EFEKTIVITAS PENERAPAN PEMBELAJARAN BERBASIS PENDEKATAN SAINTIFIK TERHADAP PRESTASI BELAJAR SISWA - Trisno Rudyat Ardi; Hadi Gunawan Sakti; Restu Wibawa (IKIP Siliwangi, 2026)
This study aimed to determine the effectiveness of implementing scientific approach-based learning on fourth-grade students’ learning achievement in Science at SDN 02 Pringgasela. The research employed a quantitative approach using a quasi-experimental method with a Non-Equivalent Control Group Design. The sample consisted of 30 students, divided into 15 students in the experimental class and 15 students in the control class. Data were collected through pretest and posttest achievement tests, supported by observation and documentation. The data were analyzed using prerequisite tests (normality and homogeneity) followed by an Independent Sample t-test at a 5% significance level. The results showed that the mean score of the experimental class (83.00) was higher than that of the control class (70.00), with a mean difference of 13 points. The t-test results indicated that t_calculated (2.5064) was greater than t_table (1.761), indicating a significant difference between the two groups. Therefore, it can be concluded that the implementation of scientific approach-based learning is effective in improving fourth-grade students’ Science learning achievement.